Method for isolating DNA - Hassan, Mohd Ali; Tabatabaei, Meisam; Zakaria @ Mamat, Mohd Rafein; Abdul Rahim, Raha; Wright, Andre-Denis G.; Shirai, Yoshihito; Abdullah, Norhani; Shamsara, Mehdi; Sakai, Kenji (2008)
The present invention provides a method for the isolation of nucleic acid from microbial cells in an environmental sample. The method includes preparing a suspension of the environmental sample, lysing the suspended sample with a buffered solution, adding sodium dodecylsufate solution to the lysed suspended sample, carrying out solvent extraction and separation to obtain an aqueous phase, reacting the aqueous phase with solvents to generate an insoluble precipitate containing nucleic acid, and isolating the nucleic acid therefrom, thereby releasing high molecular weight nucleic acid pellets from the cells.